Informational Assistance System – a Key to Self-Empowerment of Persons with Cognitive Disabilities in Manual Assembly? - Bendzioch, Sven; Hinrichsen, Sven (Human Interaction & Emerging Technologies (IHIET 2023): Artificial Intelligence & Future Applications)
The development trend in manual assembly towards increasing demands in terms of quality, variety, and cost pressure makes the transition for people with cognitive disabilities to the general labor market extremely difficult. Nevertheless, this employment sector is a central component of many activities in a sheltered workshop. Therefore, this paper investigates the use of an informational assistance system for persons with cognitive impairments to close the gap between the characteristics of this group and the operational requirements. In this way, the transition from the sheltered workshop to the general labor market will be facilitated and promoted.
Keywords: Manual Assembly; Informational Assistance System; Image Processing System; People with Disabilities